Analysis of absorption enhancement in tailor‐made periodic polycrystalline silicon microarrays. Issue 12 (3rd September 2013) - Preidel, Veit; Lockau, Daniel; Sontheimer, Tobias; Back, Franziska; Rudigier‐Voigt, Eveline; Rech, Bernd; Becker, Christiane
Abstract We present a design study of 3D photonic poly‐Si microarchitectures on 2 µm periodically textured glass substrates for application as absorber layers in crystalline Si thin‐film solar cells. Different arrays of microholes and microcones were fabricated in a low‐cost process, by combining high rate electron beam evaporation, nanoimprint technology and self‐organized solid phase crystallization. Two promising designs exhibiting strong absorption enhancement were identified by optical analysis. High angular acceptance and calculated maximum achievable short‐circuit current density of 27.6 mA/cm2 for an effective Si thickness of 1.1 µm highlight the optical potential of these microarchitectures as broadband absorbers in polycrystalline Si thin‐film solar cells. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> Tailor‐made 2 µm periodic polycrystalline silicon micro‐arrays on nanoimprint patterned glass substrates for an application as light harvesting architectures in polycrystalline Si thin‐film solar cells. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)